2012
DOI: 10.1177/0143034312445244
|View full text |Cite
|
Sign up to set email alerts
|

Traditional bullying as a potential warning sign of cyberbullying

Abstract: Although traditional bullying and cyberbullying share features in common, they differ in important ways. For example, cyberbullying is often characterized by perceived anonymity and can occur any time of the day or night. Conversely, perpetrators of traditional bullying are known to the victim, and most traditional bullying occurs at school. Yet, some researchers have suggested that involvement in the two types of bullying may be related. However, little research has modeled the system of relationships among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
149
1
10

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(183 citation statements)
references
References 26 publications
12
149
1
10
Order By: Relevance
“…Previous studies have reported an association between TB and CB experiences (e.g., Hinduja and Patchin 2008;Kowalski et al 2012), although research suggests that there are considerable gender differences in the perception, motivation, and reaction related to bullying experiences (Barlett and Coyne 2014;Wong et al 2017). There is a lack of research investigating the role of TB experiences and anger in the association between CB victimization and perpetration in respect to gender differences.…”
Section: Aims Of the Present Studymentioning
confidence: 99%
“…Previous studies have reported an association between TB and CB experiences (e.g., Hinduja and Patchin 2008;Kowalski et al 2012), although research suggests that there are considerable gender differences in the perception, motivation, and reaction related to bullying experiences (Barlett and Coyne 2014;Wong et al 2017). There is a lack of research investigating the role of TB experiences and anger in the association between CB victimization and perpetration in respect to gender differences.…”
Section: Aims Of the Present Studymentioning
confidence: 99%
“…Alonzo & Aiken, 2004;McKenna & Bargh, 2000), and others refer to it, but don't operationalized it (e.g. Kowalski, Morgan, & Limber, 2012). Thus, although PA has not been fully assimilated into anonymity research, the concept is not entirely new.…”
Section: Perceived Anonymity (Pa)mentioning
confidence: 99%
“…The hypothesis that those who encounter offline risks are more likely to encounter online risks, whether because of their personality or behaviour, is supported by survey evidence (Palfrey, Sacco, Boyd, DeBonis, 2008;Wolak, Finkelhor, & Mitchell, 2008), clinical reports (Delmonico & Griffin, 2008;Mitchell & Wells, 2007), policy analysis (Byron, 2008) and criminal cases (Child Exploitation and Online Protection Centre, 2010). Further examples include the findings that involvement in traditional bullying predicts cyberbullying (Görzig, 2011;Kowalski, Morgan, & Limber, 2012), that those who engage in more risky offline (and risky online) activities are more likely to be involved in sexting (Livingstone & Görzig, 2014) or that online and offline sex offenders show similar characteristics and tactics (Wolak & Finkelhor, 2013). Furthermore, adolescents' risk experiences do not appear to have risen with the onset of new technologies, that is, over the period when internet and mobile use have risen sharply, long term measures of harm to children reveal little or no increase over recent years (Madge & Barker, 2007;Maughan, Collishaw, Meltzer, & Goodman, 2008), and some reductions in bullying and victimization (Finkelhor, 2013, Livingstone & Smith, 2014.…”
Section: Introductionmentioning
confidence: 99%